Air pollution exposure and adverse pregnancy outcomes in a large UK birth cohort: use of a novel spatio-temporal modelling technique - Kimberly Hannam; Roseanne McNamee; Philip Baker; Colin Sibley; Raymond Agius (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: Previous work suggests an association between air pollution exposure and adverse pregnancy outcomes, even at relatively low concentrations. Our aim was to quantify the effect of air pollution having an adverse effect on preterm birth (PTB) and fetal growth in a large UK cohort using a novel exposure estimation technique [spatio-temporal (S-T) model] alongside a traditional nearest stationary monitor technique (NSTAT). METHODS: All available postcodes from a Northwest England birth outcome dataset during 2004-2008 were geocoded (N=203 562 deliveries). Pollution estimates were linked to corresponding pregnancy periods using temporally adjusted background modelled concentrations as well as NSTAT. Associations with PTB, small for gestational age (SGA), and birth weight were investigated using regression models adjusting for maternal age, ethnicity, parity, birth season, socioeconomic status (SES), body mass index (BMI), and smoking. RESULTS: Based on the novel S-T model, a small statistically significant association was observed for particulate matter (PM10) and SGA, particularly with exposure in the first and third trimesters. Similar effects on SGA were also found for nitrogen dioxide (NO_2), particulate matter (PM_2,5), and carbon monoxide (CO) in later pregnancy, but no overall increased risk was observed. No associations were found with NO_x or the outcomes PTB and reduction in birth weight. CONCLUSION: Our findings suggest an association between air pollution exposure and birth of a SGA infant, particularly in the later stages of pregnancy but not with PTB or mean birth weight change.